2019
DOI: 10.1007/s40264-019-00868-5
|View full text |Cite
|
Sign up to set email alerts
|

Reported Severe Hypersensitivity Reactions after Intravenous Iron Administration in the European Economic Area (EEA) Before and After Implementation of Risk Minimization Measures

Abstract: Introduction Severe hypersensitivity reactions (HSRs) such as anaphylaxis are of great clinical concern because of their life-threatening potential. The adverse events attributable to intravenous iron products include HSRs. An investigation by the European Medicines Agency presented in late 2013 resulted in the implementation of risk minimization measures (RMMs). Objective This study evaluated the number of severe HSRs reported for intravenous iron substances related to exposure for the 4-year periods before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 17 publications
0
24
0
2
Order By: Relevance
“…Given this pooling, the Bayesian and naïve approaches to pooling were conducted by applying a lower requirement for the standard of evidence (namely the inclusion of non-comparative studies) in order to increase the sample sizes across all arms analyzed. Despite the inclusion of non-comparative studies, the present analysis still represents a marked improvement on approaches that rely on combining data from PV and market share data, where agreement between events and exposure is extremely tenuous, doubly so when relying on proprietary market share data, which is not subject to any external scrutiny from peer reviewers, clinicians or marketing authorization holders [13,42]. Even in the case where exposure estimates could be derived from a source congruent with the event incidence data, previous analyses of HSR incidence after IV iron administration have also been confounded by highly selective use of preferred terms for HSRs and misaligned reporting periods, thereby conflating heightened post-launch vigilance and genuinely elevated incidence of HSRs [13,14,43].…”
Section: Discussionmentioning
confidence: 99%
“…Given this pooling, the Bayesian and naïve approaches to pooling were conducted by applying a lower requirement for the standard of evidence (namely the inclusion of non-comparative studies) in order to increase the sample sizes across all arms analyzed. Despite the inclusion of non-comparative studies, the present analysis still represents a marked improvement on approaches that rely on combining data from PV and market share data, where agreement between events and exposure is extremely tenuous, doubly so when relying on proprietary market share data, which is not subject to any external scrutiny from peer reviewers, clinicians or marketing authorization holders [13,42]. Even in the case where exposure estimates could be derived from a source congruent with the event incidence data, previous analyses of HSR incidence after IV iron administration have also been confounded by highly selective use of preferred terms for HSRs and misaligned reporting periods, thereby conflating heightened post-launch vigilance and genuinely elevated incidence of HSRs [13,14,43].…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitivity reactions with IV iron therapy are generally very rare, but findings have varied among different IV iron treatments. In a recent retrospective pharmacoepidemiological study comparing all available IV iron products, iron sucrose showed one of the lowest reporting rates for severe hypersensitivity, although the limitations of such analyses of pharmacovigilance data are well recognized [148]. Similarly, among patients in a study in the US Medicare non-dialysis population to compare the risk of anaphylaxis among marketed IV iron products, anaphylaxis risk was lowest for iron sucrose [149].…”
Section: Safety and Tolerability Of Iron Sucrosementioning
confidence: 99%
“…Coverage varied by country. Sales data were normalized to 100 mg dose equivalents, termed 1 defined daily dose (DDD) of iron, as has been done in similar studies of this nature [13,[28][29][30][31][32].…”
Section: Estimating Exposure To Intravenous Ironmentioning
confidence: 99%
“…iii) Anaphylactic/anaphylactoid reaction terms (anaphylactic reaction, anaphylactic shock, anaphylactoid reaction, and anaphylactoid shock), as used in two prior studies of spontaneously reported adverse reactions [31,32]. iv) Cases with a fatal outcome.…”
Section: Estimating the Incidence Of Spontaneously Reported Hypersensmentioning
confidence: 99%